The effect of ecological forest restoration on bumblebees (Bombus spp.) in the boreal forest - Spijker, Raisja (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
Insect pollinators are an important part of biodiversity, yet the number of pollinating insects is declining all over the world. Of all the wild plant species about 80% are reliant on insect pollinators, with bees being most important. One of the main causes behind the decline of insect pollinators is the loss and fragmentation of habitats. Bee species diversity is related to both cover and diversity of flowering plants. Most of the forests in Sweden are actively managed for timber production and this has an effect on the forest understory and subsequent on the insect species that occur in the forest areas. Forest restoration aims to initiate, assist or accelerate the recovery of an ecosystem. It strives to restore the presumed historical composition, structure, function, productivity and species diversity of an ecosystem present at a stand. This study aims to examine the effect of prescribed burning and gap creation, two recently introduced forest restoration and management tools, on bumblebees, flowering plants and their interactions. In 20 boreal forest stands in northern Sweden two restoration treatments, prescribed burning and artificial gap creation, were assigned in 2011, untreated stands were used as references, 15 stands were chosen for this study; 5 stands of each treatment and 5 control stands. The bumblebees were trapped using pan and window traps and the vegetation was recorded in 12 of the 15 stands. A total of 130 bumblebee individuals were caught belonging to 7 species. Bombus pratorum was the most abundant and is the most commonly found species in Sweden. In the burned stands higher number of individuals and species were caught compared to the gap cutting treatment and the control stands. An increase in abundance can be explained by the increased temperatures in the burned stand enabling the bumblebees to be more active in these areas, while using less energy. There was no difference found between the treatments and the cover and the production of blueberry (Vaccinium myrtillus) and lingonberry (Vaccinium vitis-idaea). An explanation for this is that the burning and gap cutting treatment was performed in 2011 and that during the first 2 years after a fire disturbance there is a peak in productivity in the area, which over the following year’s declines back to its original state. I show that prescribed burning can be beneficial for bumblebees, it increases their abundance and species richness compared to cap cutting and the control forests. The bumblebees were caught with two different trap types; coloured pan traps and coloured window traps; in the colours yellow, blue and white. The colour blue and yellow were the most effective colours, which could be explained by the types of flowers on the forest floor. The coloured window traps were the most effective trap type; this can be simply due to the added window; which enlarges the chance of bumblebees being caught. Window traps in the colour blue and white were the most effective method to catch bumblebees in this study. However it is best to use the colours blue, white and yellow to enhance the probability of catching different bee species. My study shows that the boreal forest is a utilized habitat by bumblebees and should thus be managed in a sustainable way. This study shows that prescribed burning is beneficial for bumblebees and this positive effect might also transcribe to other insect pollinators.